WET CUPPING EFFECTS ON PAIN AND QUALITY OF LIFE IN NON-SPECIFIC LOW BACK PAIN - Suhartono, Fathan Chandra; Sutysna, Hendra (Medicina Biomedica Journal, 2022)
BACKGROUND: Low back pain (LBP) is the most common musculoskeletal problem worldwide and is associated with disabilities that interfere with daily activities. One of the options for LBP therapy that is currently developing is cupping therapy. This study aims to determine the effect of cupping therapy on the pain scale and quality of life in patients with non-specific LBP.METHODS: This research used a comparative analysis design. The research was carried out by observation, with a cohort study approach. The research subjects were 14 people who were taken by consecutive sampling method. Data were analyzed using paired t-test or the Wilcoxon test.RESULTS: Wilcoxon's test showed a significant change on the pain scale (p=0.001). Through the Wilcoxon test, it was found that only physical function (p0.001) and pain (p=0.001) had significant changes in quality of life, and through paired t-test, only general health had significant differences (p=0.004).CONCLUSION:Cupping therapy significantly affects changes in pain scale, but not on the overall quality of life.